Discrete Wavelet Transform (DWT) Based Dual Watermarking For Authentication And Copyright Protection - Lim, Chen Gen (2023)
Digital media faces significant challenges related to unauthorized access, manipulation, and copyright infringement, necessitating effective authentication and copyright protection mechanisms. This thesis proposes a novel dual watermarking scheme based on the Discrete Wavelet Transform (DWT) to address these concerns. The primary objective of the proposed scheme is to provide robust copyright protection. A watermark, carrying ownership and copyright information, is embedded in the spatial domain using the DWT. This watermark acts as a digital signature, enabling the identification and tracing of the rightful owner of the content. The frequency domain embedding enhances the watermark's robustness against common attacks. In addition to copyright protection, the scheme incorporates a fragile watermark for authentication purposes. The fragile watermark is embedded in the least significant bit which is highly sensitive to any modifications or tampering. By extracting and comparing the fragile watermark, the integrity and authenticity of the content can be verified. Comprehensive experimental evaluations have been conducted to assess the performance of the proposed dual watermarking scheme. The results demonstrate its effectiveness in providing robust copyright protection and authentication capabilities. The scheme exhibits high imperceptibility, preserving the visual quality of the watermarked content, while ensuring a high level of sensitivity to unauthorized alterations.